RANCANGAN LABORATORIUM TERINTEGRASI AKADEMI TEKNIK DAN KESELAMATAN PENERBANGAN (ATKP SURABAYA) - M. Amin Bakri (JREC (Journal of Electrical and Electronics), 2012)
The development of telecommunications, computers and electronics technology (Telematics), has provided much positive impact on education management. One of those benefits is the growing use of technology to support the automation, integration, and centralized management of learning systems, both in the classroom, laboratory, and the use ofvirtual environments (e-learning). This paper addresses to explore process of developing Integrated information -based Laboratory at Akademi Teknik dan Keselamatan Penerbangan (ATKP Surabaya). In addition to discussing the concept and system architecture, also analyzed the development and implementation on the ground. In fact, the i mplementation process is summed up efforts are still needed repairs and improvements, especially from non-technical factors such as change management.